154 DIABETES SCREENING IN THE EMERGENCY DEPARTMENT. (1st January 2006) - Shin, E. C.; Qazi, M.; Lewis, R.; Charfen, M.
Abstract : Introduction: Many individuals at risk for type 2 diabetes mellitus (DM2) who do not have access to primary care present to the emergency department (ED) for unrelated illnesses. The ED visit may represent an opportunity to screen these individuals for DM2. The primary purpose of this ongoing study is to identify specific clinical characteristics and laboratory findings in the ED that can be used to screen individuals at risk for DM2. Methods: Patients 18-80 years of age in a county ED are enrolled if they meet one of the following inclusion criteria: (1) a random blood sugar level ≥ 140 mg/dL, (2) a blood sugar level ≥ 126 mg/dL more than 2 hours after a meal, or (3) two risk factors, which include family history DM2, estimated body mass index (BMI) ≥ 25 kg/m 2, ≥ 45 years of age, and high-risk ethnicity. Patients were excluded if they had previously been diagnosed with diabetes (including during initial ED visit) or possessed comorbid conditions, such as use of steroids in the past month, that would interfere with accurately identifying patients at high risk for DM2. During the ED visit patients are scheduled for a follow-up visit 6 weeks later during which an oral glucose tolerance test (OGTT) is administered. Patients who test positive for diabetes are asked to return for a second confirmatory OGTT. Results: To date 291 patients have enrolled in the study. Preliminary results show that 122/291 (41%) completed their first follow-up visit. Of returnees 56% were Hispanic. The median age (IQR) and BMI were 50.7 (42.4-56.9) years and 30.3 (21.2-39.5) kg/m 2, respectively. Remarkably, 68% of subjects had abnormal glucose homeostasis: 8/122 (6.6%) tested positive for DM2, 30/118 (25%) had impaired fasting glucose alone (IFGa), 11/118 (9%) had impaired glucose tolerance alone (IGTa), and 34/118 (29%) had IFG and IGT. Evaluation of a subgroup (55/122) confirmed that 75% (41/55) had no primary care provider. Conclusion: Preliminary results show a high percentage of patients tested positive for DM2 or prediabetes. This suggests that ED patients may benefit from targeted screening for DM2.